Assessment of Potential Risks of Regional for Global Financial Security - Bokovnya, Alexandra Yuryevna; Ilduzovna Khisamova, Zarina; Vasyukov, Vitalii Fedorovich; Rustamovich Begishev, Ildar (Cuestiones Políticas, 2020)
The objective of the research was to assess the potential risks of stable CBDC digital currencies,alsoknown as coins, for global financial security.. For several years we have seen the phenomenon of "de-dollarization" in the international financial market; this is a gradual transition in abandoning the use of the US dollar in central bank payments and reserves. A key step in the strategy of freeing countries from the US dollar was the creation of national digital currencies, i.e. stable CBDC currencies. To systematize the data obtained, methods of functional and institutional classification, statisticalanalysisand, also, retrospective, currentand future methods of analysis and synthesis of theoretical and practical material were used.. It is concludedthat the rejection of the stable currency Libra was motivated by the possibility of its transformation into a competing system of traditional currencies. The emergence of a private CBDC prompted central banks and regional associations to create their own CBDCs that could compete with the US dollar in international payments. However, the emergence of CBDC is associated with undeniable advantages and objective risks to the existing financial system and its security.